Гидродинамика структуры потока жидкости в циркуляционном аппарате со струйно-инжекционным газонаполнением - Ведь, В. В. (НТУ "ХПИ", 2013)
Розроблена модель гідродинаміки структури потоку рідини в циркуляційному апараті зі струменеві-інжекційним газонаповненням. Показано, що апарат можна поділити на дифузійні зони та зону ідеального змішання. Отримана передаточна функція апарату, аналіз якої дозволить визначити вплив поздовжнього змішання на структуру потоку і може бути використана при розрахунку масопереносу в апараті.

The model of the hydrodynamics structure of the liquid flow in the circulation apparatus with jet-injection gas filling was achieved. It is shown that the apparatus can be divided into the diffusion zone and the perfect mixing zone. The transfer function of the system was defined, the analysis of which will determine the effect of longitudinal mixing on the flow structure and can be used for calculation of mass transfer of the apparatus.
Hydrodynamics structure of the flow liquid in the circulation apparatus with jet-ijection gas filling
Keywords: высокоинтенсивные аппараты; энергия жидкости; жидкая фаза; химическая технология